Bright Light‐Emitting Diodes Based on Organometal Halide Perovskite Nanoplatelets. Issue 2 (17th November 2015) - Ling, Yichuan; Yuan, Zhao; Tian, Yu; Wang, Xi; Wang, Jamie C.; Xin, Yan; Hanson, Kenneth; Ma, Biwu; Gao, Hanwei
Abstract : Bright light‐emitting diodes based on solution‐processable organometal halide perovskite nanoplatelets are demonstrated. The nanoplatelets created using a facile one‐pot synthesis exhibit narrow‐band emissions at 529 nm and quantum yield up to 85%. Using these nanoparticles as emitters, efficient electroluminescence is achieved with a brightness of 10 590 cd m −2 . These ligand‐capped nanoplatelets appear to be quite stable in moisture, allowing out‐of‐glovebox device fabrication.